Efficacy of a group therapy on quality of life and emotional state in breast cancer women - Bellver, Ascensión (Psicooncología, 2008)
Objective: The aim of this study was to evaluated the efficacy of group psychotherapy interventions on quality of life and its impact on distress response of women with breast cancer. Furthermore, we analyzed the differences between two types of group psychotherapy in the same variables. The group interventions consisted on six weekly sessions, one group was working self-esteem and communication abilities, and the other was training cognitive behavioural techniques. Methods: The sample consisted of 91 women with non-metastatic breast cancer who received group psychotherapy after medical treatment. The age mean was 49.5 + 8.2 with age range between 31 and 74 years. The most women were married 82%. The women were divided into two groups: self-esteem and com munication abilities (n=42) and cognitive behavioral therapy (n=49). The women completed the Functional Assessment of Cancer Therapy-Breast FACT-B (4th version) and the Hospital Anxiety and Depression Scale (HADS) at the beginning and the end of group psychotherapy and three mounts follow up. The statistical analyses were MANOVA repeated-measures and design factorial mixed. Results: The results showed statistical significant improvements of group psychotherapy in anxiety and depression (p
Keywords: Group psychotherapy; Quality of life; Mood state; Breast cancer